2000
DOI: 10.1099/00207713-50-2-451
|View full text |Cite
|
Sign up to set email alerts
|

Alicyclobacillus hesperidum sp. nov. and a related genomic species from solfataric soils of São Miguel in the Azores.

Abstract: Several acidophilic, slightly thermophilic or thermophilic Gram-positive isolates were recovered from solfataric soil at Furnas on the Island of Sa 4 o Miguel in the Azores. Phylogenetic analysis of the 16S rRNA gene sequence showed that these organisms represented two novel species of the genus Alicyclobacillus. Strains FR-11 T and FR-1b had an optimum growth temperature of about 50 SC, whereas strains FR-3 and FR-6 T had an optimum growth temperature of about 60 SC. Biochemical, physiological and chemotaxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 33 publications
1
42
1
3
Order By: Relevance
“…Simple v-cyclohexane acids were also identified from the published data (Oshima & Ariga, 1975) and oxyacids by specific fragmentation of Me-TMS derivatives (methyl-O-trimethylsilyl derivatives) and methyl esters (without silylation). It was shown that strain K1 T differed only slightly from A. acidocaldarius, A. acidoterrestris, Alicyclobacillus acidiphilus, Alicyclobacillus sendaiensis, Alicyclobacillus hesperidum (Wisotzkey et al, 1992;Goto et al, 2003;Matsubara et al, 2002;Tsuruoka et al, 2003;Albuquerque et al, 2000), S. disulfidooxidans (Dufresne et al, 1996) and strains of S. thermosulfidooxidans (Tsaplina et al, 1994). All these strains contained v-alicyclic (cyclohexanoic) fatty acids as the major lipid component.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simple v-cyclohexane acids were also identified from the published data (Oshima & Ariga, 1975) and oxyacids by specific fragmentation of Me-TMS derivatives (methyl-O-trimethylsilyl derivatives) and methyl esters (without silylation). It was shown that strain K1 T differed only slightly from A. acidocaldarius, A. acidoterrestris, Alicyclobacillus acidiphilus, Alicyclobacillus sendaiensis, Alicyclobacillus hesperidum (Wisotzkey et al, 1992;Goto et al, 2003;Matsubara et al, 2002;Tsuruoka et al, 2003;Albuquerque et al, 2000), S. disulfidooxidans (Dufresne et al, 1996) and strains of S. thermosulfidooxidans (Tsaplina et al, 1994). All these strains contained v-alicyclic (cyclohexanoic) fatty acids as the major lipid component.…”
mentioning
confidence: 99%
“…Strain K1 T grew optimally at 37-42 u C, differing from the known thermophilic bacteria of the genus Alicyclobacillus, which are characterized by optimal growth at 42-60 uC and Dufresne et al, 1996); 3, A. acidocaldarius subsp. acidocaldarius DSM 446 T (Wisotzkey et al, 1992); 4, A. acidoterrestris DSM 3922 T (Wisotzkey et al, 1992); 5, A. cycloheptanicus DSM 4006 T (Wisotzkey et al, 1992); 6, A. hesperidum DSM 12489 T (Albuquerque et al, 2000); 7, A. acidiphilus TA-67 T ; 8, A. herbarius DSM 13609 T ; 9, A. pomorum DSM 14955 T (Goto et al, 2003); 10, A. sendaiensis ATCC BAA-609 T (Tsuruoka et al, 2003). +, Positive result; 2, negative result; W, weakly positive; ND, not determined.…”
mentioning
confidence: 99%
“…The possession of ω-cyclohexane fatty acid as the major acid distinguishes the isolate from A. cycloheptanicus and A. herbarius, which possess ω-cycloheptane fatty acid as the major acid. ω-Alicyclic acid is unique H. Matsubara and others Albuquerque et al (2000).…”
Section: Characteristicmentioning
confidence: 99%
“…k j k j j Growth in 5 % NaCl k k j k k Growth with lysozyme present j k k  k Acid production from : Albuquerque et al (2000).…”
Section: Characteristicmentioning
confidence: 99%
See 1 more Smart Citation